2005
DOI: 10.1016/j.parco.2005.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Racoon: A parallel mesh-adaptive framework for hyperbolic conservation laws

Abstract: We report on the development of a computational framework for the parallel, mesh-adaptive solution of systems of hyperbolic conservation laws like the timedependent Euler equations in compressible gas dynamics or Magneto-Hydrodynamics (MHD) and similar models in plasma physics. Local mesh refinement is realized by the recursive bisection of grid blocks along each spatial dimension, implemented numerical schemes include standard finite-differences as well as shock-capturing central schemes, both in connection w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 32 publications
(37 reference statements)
0
56
0
Order By: Relevance
“…In order to reduce the overhead, some authors have suggested a block-wise approach to SAMR [6][7][8][9][10][11], with the purpose to avoid the clustering and grid-fitting steps in the Berger-Colella approach. The initial, coarse grid is divided into a number of blocks.…”
Section: Approaches To Structured Adaptive Mesh Refinementmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to reduce the overhead, some authors have suggested a block-wise approach to SAMR [6][7][8][9][10][11], with the purpose to avoid the clustering and grid-fitting steps in the Berger-Colella approach. The initial, coarse grid is divided into a number of blocks.…”
Section: Approaches To Structured Adaptive Mesh Refinementmentioning
confidence: 99%
“…Also the Racoon framework has been parallelized in two levels but using a hybrid of MPI and POSIXPthreads [6].…”
Section: Software Framework For Samrmentioning
confidence: 99%
See 2 more Smart Citations
“…An overall summary of AMR for both the Euler and Navier-Stokes Equations was presented in several publications [45,46,47]. In addition to studying numerical schemes on an adaptively refined mesh, the most recent interests were focused on improving AMR parallel efficiency [48,49,50,51,52], applying AMR to practical problems [53,54,55,56] and presenting new AMR frameworks [57,58,59].…”
Section: Adaptive Mesh Refinementmentioning
confidence: 99%